1981
DOI: 10.1351/pac198153020377
|View full text |Cite
|
Sign up to set email alerts
|

The life-cycle of the two phase system in vinyl chloride polymerisation

Abstract: Photon correlation spectroscopy (PCS) was used to obtain information on the state of the two phase system following phase separation in the very early stages of vinyl chloride polymerisation.Around a gel phase volume ratio of 103 the particle number appeared constant with the particles growing at constant rate until a sudden decrease in numbers set in at a certain particle size, indicating flocculation. A simple mathematical model is given to account for the observations. From this work and earlier studies a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1984
1984
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…Formation of primary particles has been studied by many investigators (16, [59][60][61][62][63][67][68][69][70][71][72][73][74][75][76][77]. From turbidimetric measurements, Boissel, et al (63), suggested that polymer precipitates from the monomer phase at conversions a s low as 0.001 %.…”
Section: Physical Phenomenamentioning
confidence: 99%
“…Formation of primary particles has been studied by many investigators (16, [59][60][61][62][63][67][68][69][70][71][72][73][74][75][76][77]. From turbidimetric measurements, Boissel, et al (63), suggested that polymer precipitates from the monomer phase at conversions a s low as 0.001 %.…”
Section: Physical Phenomenamentioning
confidence: 99%
“…Assuming that the ionic species of the unknown electrolyte present in the pure VCM is a 1:1 electrolyte, and that the corresponding ions have ion mobilites in the same order of magnitude as Bu4 N+ and BFT, the concentration of ions in the "pure" VCM was estimated as I tmml/1. This ion concentration corresponds to a reciprocal Debye length of around 1 x 107 1 --m-. The reader should note that the assumptions underlying this calculation have no direct experimental verification.…”
Section: Debye Length and Particle Stabilitymentioning
confidence: 99%
“…These particles have an initial size of about 0.1 ~rn [1], and they are stabilized by electrostatic forces during a certain growth period after their formation [2,3]. The size and number of particles formed are closely connected with the particle stability [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Not being soluble in its own monomer, PVC macromolecules precipitate, forming coils very close to each other, because the transfer reaction time is much shorter than the time it takes the macromolecules to diffuse away, according to calculations performed by several researchers (Rance and Zichy, 1981). As a consequence, the coils tend to flocculate and form so-called basic particles, with a diameter that has been estimated around 0.01-0.02 m (Allsopp, 1981;Rance and Zichy, 1981). The latter step can be considered the nucleation step of a process of growth of PVC particles in each droplet both by agglomeration and by polymerization.…”
Section: Vcm Suspension Polymerization Overviewmentioning
confidence: 99%